HDAC6 inhibitor WT161 induces apoptosis in retinoblastoma cells and synergistically interacts with cisplatin - Sun, Jun; Qian, Xia; Zhang, Feifei; Tang, Xiaofeng; Ju, Cheng; Liu, Renfeng; Zhou, Ruihao; Zhang, Zhiping; Lv, Xiao-Bin; Zhang, Changhua; Huang, Guofu (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: WT161 is a recently discovered histone deacetylase 6 (HDAC6) inhibitor which shows anti-tumor effects on multiple myelomas and breast cancer. However, the role of WT161 in retinoblastoma remains unclear. The aim of this study is to explore the role of WT161 in retinoblastoma and its underlying mechanisms. Methods: The anti-proliferation of WT161 on retinoblastoma cells was examined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and soft agar colony formation assay. Cell apoptosis was analyzed using flow cytometer. WT161 and DDP synergistic effect was evaluated by isobologram analysis using CompuSyn software. Results: WT161 suppressed the cell growth and induced apoptosis of retinoblastoma cells in a dose- and time-dependent manner. Mechanistically, WT161 increases the transcription of Bad through activating Bad promoter. Chromatin immunoprecipitation (ChIP) assay showed WT161 treatment increased acetylated histone H3 (AcH3) and acetylated histone H4 (AcH4) on the Bad promoter in retinoblastoma cells. In addition, WT161 shows synergistically inhibitory effects on retinoblastoma cell combined with cisplatin. Conclusions: These results indicate that WT161, as a selective HDAC6 inhibitor, is a promising agent against retinoblastoma.